CODE CHOICE USED BY THE EMPLOYEES IN THE COMMUNICATION WITH THE SUPERIOR AND THE CO-WORKER - Eunike Wiguna; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2016)
This study is about the choice of codes used by the employees in communicating with their superior and their co-worker. The thing that has caught the writer’s attention and curiosity to write on this particular topic is the language that is used by the employees in a work place like switching when they talk to the superior and the co-worker. The aims of this study were to describe and to analyze the codes which were used by the employees, to find out the dominant code they chose, and to explain what factors affected their choice of code. Through the analysis, the writer found that the employees chose to use standard or casual Indonesian codes in communicating with their superior. Whereas they used Javanese codes in communicating among themselves.